INTERLAYER VERBALIZATION OF TOPONYMS IN UZBEK AND GERMAN LANGUAGES - Anarkulov, Sanjar Iskandarovich (International Journal of Psychosocial Rehabilitation, 2020)
Geographical names-toponyms of each nation are formed over the centuries and are inextricably linked with its history and culture,created in different eras, as cultural and historical evidence, they are monuments of their time, as well as works of great masters and nameless examples of folk art. Historical geographical names need to be protected, catalogued, and studied. Geographical names-the names of our cities and villages, mahallas, streets and squares, channels, rivers and other objects are a collective work of folk genius. They serve as landmarks in time and space, creating the historical and cultural image of the country.